A Dual Role for the OsK5.2 Ion Channel in Stomatal Movements and K+ Loading into Xylem Sap. Issue 4 (16th June 2017) - Nguyen, Thanh Hao; Huang, Shouguang; Meynard, Donaldo; Chaine, Christian; Michel, Rémy; Roelfsema, M. Rob G.; Guiderdoni, Emmanuel; Sentenac, Hervé; Véry, Anne-Aliénor
Abstract : The rice K + channel OsK5.2 is necessary for rapid stomatal closure and contributes to shoot K + supply from the root, thus highlighting the differing functional distribution of Shaker channels compared to Arabidopsis. Abstract: The roles of potassium channels from the Shaker family in stomatal movements have been investigated by reverse genetics analyses in Arabidopsis ( Arabidopsis thaliana ), but corresponding information is lacking outside this model species. Rice ( Oryza sativa ) and other cereals possess stomata that are more complex than those of Arabidopsis. We examined the role of the outward Shaker K + channel gene OsK5.2. Expression of the OsK5.2 gene ( GUS reporter strategy) was observed in the whole stomatal complex (guard cells and subsidiary cells), root vasculature, and root cortex. In stomata, loss of OsK5.2 functional expression resulted in lack of time-dependent outward potassium currents in guard cells, higher rates of water loss through transpiration, and severe slowdown of stomatal closure. In line with the expression of OsK5.2 in the plant vasculature, mutant plants displayed a reduced K + translocation from the root system toward the leaves via the xylem. The comparison between rice and Arabidopsis show that despite the strong conservation of Shaker family in plants, substantial differences can exist between the physiological roles of seemingly orthologous genes, as xylem loading depends on SKOR and stomatal closure on GORK in Arabidopsis, whereas both functions are executed by the single OsK5.2 Shaker in rice.